Activating Mutations of FLT3 Gene in Childhood Acute Myeloid Leukemia and Their Applications for Detection of Minimal Residual Disease - GOTO, Hiroaki; YAMAZAKI, Sakurako; KAI, Sumio; FUJII, Hisaki; IKUTA, Koichiro; TAKAHASHI, Hiroyuki; KUROKI, Fumiko; OKUDA, Kumiko (The Japanese Journal of Pediatric Hematology, 2005)
Forty-two children with acute myeloid leukemia (AML) were screened for two activating mutations of the FLT3 gene, internal tandem duplication (ITD) and Asp 835 substitution (D835), using polymerase chain reaction (PCR). ITD and D835 were detected in 8 (19.0%) and 3 (7.1%) patients, respectively. Although no difference was found in the remission rate between ITD-positive and -negative patients (100% vs. 81%, p= 0.32), the relapse rate of ITD-positive patients was significantly higher than that of ITD-negative patients (87.5 ± 11.7% vs. 40.1 ± 10.5%, p = 0.0435). Interestingly, among 7 patients with t (8; 21), 3 cases were positive for ITD and all those cases experienced relapse while only one out of 4 ITD-negative cases experienced it. Thus, ITD may detect patients with poor prognosis in AML with t (8; 21). For D835-positive AML, we could not clarify the clinical significance because of its low positivity. Minimal residual leukemic cells in patients with remission could be detected effectively by PCR using the patient's ITD sequence-specific primer. The results obtained from ITD-specific PCR were closely correlated with those of reverse transcription-PCR for AML1-MTG8 or PML-RARA in patients with t (8; 21) or t (15; 17). Thus, ITD-specific PCR would be a useful method for the detection of minimal residual disease (MRD) in patients with ITD-positive AML who have no other applicable MRD targets.